Economic analysis of fish production using different feed types practiced in Dhanusha district, Nepal - Subedi, Pritee; Pandit, Narayan Prasad; Mahato, Naresh Kumar; Karki, Mahesh; Uprety, Anupam (Journal of Agriculture and Natural Resources, 2019)
A study on the economic analysis of fish production using different feed types practiced in Dhanusha district was conducted in 2018. Out of 600 fish farmers, sixty fish farmers(10%) from the Fish Superzone region i.e. Janakpur sub-metropolitan city, Bideh municipality, Sahidnagar municipality, Kamala municipality, Hanspur municipality, Janaknandani rural municipality and Aaurahi  rural municipality, selected using simple random sampling, were surveyed using semi-structured questionnaire. The study revealed that locally formulated mash feed was commonly used feed type in which rice bran and mustard oil cake (RB+MOC) was the principle feed ingredient. 55% of the farmers used rice bran and mustard oil cake (RB+MOC), 20% used rice bran, mustard oil cake and soybean (RB+MOC+SOB), 10% used rice bran, mustard oil cake and fish meal (RB+MOC+FM) and 15% farmers mineral and vitamin (RB+MOC+MIN/VIT) in their feed formulation. The productivity of the fish production in feed type RB+MOC+SOB (3.41±1.02) was significantly higher than other feed type.  The total variable cost per ha (5.23±2.11) was found significantly(p